PENGARUH MEKANISME TATA KELOLA PERUSAHAAN TERHADAP KINERJA - Eko Budi Santoso (Fakultas Bisnis UKDW, 2010)
Good Corporate Governance is a major issue dealing with agency problem. The purpose of this study is to analyse the development of good corporate governance in Indonesia. The result of the study show inverse effect between board structure and board independence towards performance. This difference indicates the need of good checks and balances mechanism. This study also explains the failure of two-tier board system as governance to sustain Indonesian companies during the crisis. Keywords:Corporate governance, ownership structure, board structure, board independence, two-tier board system.